2006
DOI: 10.1021/ol061098a
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Biomimetic Nanocatalyst for Cleaving Phosphoester and Carboxylic Ester Bonds under Mild Conditions

Abstract: [Structure: see text] As a result of the unique surface structure of nanospheres, Asp and His residues supported on a 12 nm maghemite nanoparticle worked collaboratively as a biomimetic nanocatalyst for hydrolyzing paraoxon (phosphoester) and 4-nitrophenyl acetate (carboxylic ester) in Milli-Q water (pH 7.0) at 37 degrees C, without employing extremes of pH or heavy metals. Our nanocatalyst could be facilely recovered via magnetic concentration. The isolated catalyst exhibited long-term stability, showing no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
3
30
0
Order By: Relevance
“…The various types of organic reactions using the MNPs-supported catalysts that have emerged recently include C-C coupling reactions [17][18][19][20][21][22][23][24], hydroformylation [25,26], hydrogenation [27][28][29][30][31][32][33][34][35], C-N coupling reaction [36,37], oxidation [38][39][40][41][42][43], cleavage of allyl esters and ethers (deallylation catalyst) [44], enantioselective acylation [45], multicomponents Aza-Sakurai reaction [46], the Paal-Knorr reaction [47], CO 2 cycloaddition reactions [48], asymmetric hydrosilylation of ketones [49], and esterification [50]. Other reports of MNPs-supported catalysts include O-Alkylation reaction [51], halogen exchange reaction [52], polymerization reactions [53], enzymes for carboxylate resolution [54], amino acids for ester hydrolysis [55], organic amine catalysts promoting Knoevenagel [56], one-pot reaction cascades [57], and the various acidcatalyzed reactions (deprotection reaction of benzaldehyde dimethylacetal) [58]. Concerning the Suzuki coupling reactions, palladium complexes...…”
Section: Introductionmentioning
confidence: 99%
“…The various types of organic reactions using the MNPs-supported catalysts that have emerged recently include C-C coupling reactions [17][18][19][20][21][22][23][24], hydroformylation [25,26], hydrogenation [27][28][29][30][31][32][33][34][35], C-N coupling reaction [36,37], oxidation [38][39][40][41][42][43], cleavage of allyl esters and ethers (deallylation catalyst) [44], enantioselective acylation [45], multicomponents Aza-Sakurai reaction [46], the Paal-Knorr reaction [47], CO 2 cycloaddition reactions [48], asymmetric hydrosilylation of ketones [49], and esterification [50]. Other reports of MNPs-supported catalysts include O-Alkylation reaction [51], halogen exchange reaction [52], polymerization reactions [53], enzymes for carboxylate resolution [54], amino acids for ester hydrolysis [55], organic amine catalysts promoting Knoevenagel [56], one-pot reaction cascades [57], and the various acidcatalyzed reactions (deprotection reaction of benzaldehyde dimethylacetal) [58]. Concerning the Suzuki coupling reactions, palladium complexes...…”
Section: Introductionmentioning
confidence: 99%
“…25 Key to the successful application of MNPs is the surface functionalization. There are two general surface modification approaches taken: (1) Molecules containing functional groups such as carboxylic acids or phosphoric acids are attached through noncovalent reversible absorption on MNPs; 22,28,29 although this approach is conceptually simple, the presence of a functional group does not guarantee that a ligand will remain bound to the surface of a nanoparticle at various stages of surface modification and during application. In fact, the loss of catalytic activities of MNP supported catalyst was attributed to the dissociation of catalysts from MNP surface.…”
Section: Introductionmentioning
confidence: 99%
“…Major methods in synthesis of organic molecule-immobilized magnetically retrievable catalysts (MRCs) focus on traditional strategies, in which organic catalysts or ligands are bonded onto the surface of magnetic nanoparticles (MNPs) or SiO 2 -supported MNPs. Earlier research in supporting of organic molecule onto Fe 2 O 3 MNPs was reported by Gao group [43] at 2006. As shown in Scheme 1, they used dopamine as a linker for immobilization of two amino acid residues (Asp and His residues, which have a carboxylate group and an imidazole molecule on side chains, respectively).…”
Section: Organic Catalysts Immobilized On Magnetic Nanoparticlesmentioning
confidence: 95%